2015 Addendum to financial accounting and reporting : standards and applications : volume 1 - Cabrera, Ma. Elenita Balatbat; Ocampo, Reynaldo R. (Manila, Philippines : GIC Enterprises & Co. Inc., 2015)
This 2015 Addendum sets out the effect of the recently approved International Financial Reporting Standards and their related consequential amendments on the topics covered in the 2013-2014 Edition of the Financial Accounting and Reporting, Volume 1.
Financial Instruments Framework -- Receivables - Part I. -- investment in Equity Instruments -- Investment in Debt Instruments and other financial Assets -- Agricultural Assets.
Keywords: ACCOUNTING